Kinetics of Oxidation of Alanine by Pyridiniumdichromate in The Presence of Perchloricacid Medium in DMSO-H2O (v/v) medium by Spectrophotometric method - S., Rajakumari; S., Chitradevi; S, Ramadevi; S., Hari kumar (International Journal of Psychosocial Rehabilitation, 2020)
Kinetics of oxidation of alanine by pyridiniumdichromate (PDC) has been studiedspectrophotometrically in the presence of perchloric acid in DMSO-H2O 50% (v/v) medium. The reaction was first order dependence on PDC, alanine and fractional order with respect to H+. The effect of solvent composition indicates that the reaction rate increases with an increase in the polarity of the medium. No significant effect was observed by added salts. The main oxidation product of L-alanine has been identified as corresponding carbonyl compound. The reaction does not induce the polymerization of acrylonitrile. The reaction has been investigated at different temperature and activation parameters were calculated.